On the temporal evolution of turbopause altitude, 1996–2021, 70°N, 19°E. (4th June 2021) - Carley, Jacob; Hall, C. M.; Nozawa, S.
Abstract: Medium frequency radars with multiple receivers are able to track the movement of the interference pattern on the ground from echoes from irregularities in refractive index. In particular, refractive index in the mesosphere is determined by electron density – commonly known as the ionospheric D-region. Thus using this technique it is possible to determine winds in the height regime 70-90 km, depending on the degree of ionization throughout the year. In addition, by examining the fading times of the passage of these structures, it is possible to deduce metrics pertaining to neutral air turbulence. Here, we employ a well-established method to this effect. Thereafter, comparing the turbulent intensity to the kinematic viscosity of the neutral atmosphere, we determine the turbopause altitude. Above this height, atmospheric constituents behave independently, whereas below, all components are mixed. Contrary to earlier analyses, we present evidence the turbopause altitude has been constant since approximately 2004.